2019
DOI: 10.1016/j.ygyno.2019.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in gynecologic cancer genetics evaluation

Abstract: An estimated 2-5% of endometrial cancers and 15-20% of high-grade, non-mucinous epithelial ovarian cancers have an underlying hereditary cause. Appropriate risk assessment, genetic counseling, and germline genetic testing for cancer predisposition genes in both gynecologic cancer patients and their at-risk relatives is essential for effective delivery of tailored cancer treatment and cancer prevention. However, significant disparities exist within medically underserved and minority populations in the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 62 publications
(79 reference statements)
3
34
0
2
Order By: Relevance
“…Overall, we found that germline and somatic BRCA1/2 mutations had prevalence rates of 20.3 and 4.1%, respectively. Disparities in both germline and somatic testing exist (44,45). Regarding other Chinese studies, our germline mutation prevalence approximated the values reported by Li (35).…”
Section: Discussionsupporting
confidence: 84%
“…Overall, we found that germline and somatic BRCA1/2 mutations had prevalence rates of 20.3 and 4.1%, respectively. Disparities in both germline and somatic testing exist (44,45). Regarding other Chinese studies, our germline mutation prevalence approximated the values reported by Li (35).…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have identified several barriers to genetic counseling and to obtaining accurate family histories. These include a lack of awareness of the goal of having genetic services, inaccurate cancer risk perception, poor communication, limited knowledge of family histories, and time commitments to both travel to and attend genetics or other medical appointments . There is further controversy regarding the appropriate time for undergoing counseling.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that since 2015, the D99 exemption code has been introduced, which permits free access to the surveillance program for healthy women at high risk because they are BRCA gene mutation carriers. Therefore all issues related to individuals with genetic variants should be understood and made explicit to all health operators to have the possibility of intervention on the economic resources to target inherited breast cancer, as well as the related human, psychological, genetic, and management issues [123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142].…”
Section: Discussionmentioning
confidence: 99%